Agrobiodiversity and diets: food access and seasonality in Solomon Islands - Nabuuma, Deborah; Kabu, Rosely; Moyo, Marcelius; Ekesa, Beatrice (2025)
Presented at the 3rd International Agrobiodiversity Congress, Kunming, China, May 20-22, 2025. Agrobiodiversity is vital for food security and resilience in Pacific Island states, which face food insecurity, triple burdens of malnutrition, and climate change impacts. Understanding food access and seasonality can inform utilization of local agrobiodiversity to improve diets and food system resilience. This was explored in a mixed methods study, survey of 122 households and twelve focus group discussions (97 men, 86 women) from 10 communities in Malaita, Solomon Islands. Women’s diets were inadequate with an average consumption of 2.3 food groups. The most consumed groups were starchy staples (87%), dark green leafy vegetables (51%), and meat and fish (33%), largely sourced from own production (67%, 86%, and 61%, respectively). Main food groups bought included legumes (100%), animal sourced foods (34%) and starchy staples (28%). Level of food availability and sourcing varied with food item and community. Across food groups, households were more likely to maintain the same level of purchase or reduce it, if income increased, except for grains. Household food purchase was influenced by food needs, convenience, and preference. Seasonal food calendars for 3 regions of Malaita reflected a wide range of foods, fruits, vegetables and animal source foods had the highest diversity, while grains had the least diversity within a food group, and nuts had the largest availability gaps. A variety of foods is available to create a diverse food basket, yet current consumption is inadequate. Understanding barriers to food access and consumption is essential for designing effective agrobiodiversity interventions and nutrition behavior change strategies that enhance dietary diversity and health outcomes.